Framework on risk prioritisation of mycotoxins in food: a case study in two wheat-based products - Suman, Michele; Oboeuf, Maxence; Abdallah, Mohamed Fathi; Hazel, C.; Varga, Elisabeth; Mally, Angela; Medina, Angel; Molero, M.; Sansom, Annette; Korzeniowski, Konrad J. (De Gruyter, 2025)
In its simplest form, risk is the product of hazard, i.e. toxic potency of a chemical substance, and exposure, or dose. Hazard-based decision-making is based solely on hazard without any consideration of exposure. The development of mitigation strategies should prioritise mycotoxins that regularly occur at undesirable levels in commonly consumed commodities, wherein both the toxicological profiles and effectiveness of mitigation are understood with a reasonable degree of certainty. This manuscript presents a framework for risk prioritisation of mycotoxins in food, integrating hazard assessment, exposure evaluation, and for the first time appraisal of mitigation strategies. More specifically, by (1) identifying the mycotoxins relevant for each food categories, by (2) assigning a severity score for the pivotal effect of each mycotoxin; by (3) calculating the respective food-categories’ contributions to the combined exposures and by (4) assessing the existing mitigation strategies, the framework aims to prioritise mycotoxins based on their health risks and potential for effective risk mitigation. As a proof of concept, the framework was applied in two wheat-based food commodities – bread and pasta –, focusing on Ochratoxin A (OTA), Deoxynivalenol (DON), and Zearalenone (ZEN), revealing that OTA in bread is the highest priority concern, followed by DON in bread.
Keywords: risk prioritisation; mitigation; mycotoxins; deoxynivalenol; Ochratoxin A; zearalenone; pasta-; bread; 3214 Pharmacology and Pharmaceutical Sciences; 31 Biological Sciences; 32 Biomedical and Clinical Sciences; 2.2 Factors relating to the physical environment; 3107 Microbiology; 3214 Pharmacology and pharmaceutical sciences